KUAT TEKAN BETON MUTU TINGGI MENGGUNAKAN KOMPARASI AGREGAT GAMALAMA, AGREGAT MERAPI DAN AGREGAT KALI PROGO - Hakas Prayuda; As’at Pujianto (Jurnal Riset Rekayasa Sipil, 2018)
This study discusses the comparison of the compressive strength of concrete using various types of fine and coarse aggregate origin from three different locations. Fine and coarse aggregates are taken from Mount Gamalama, North Maluku Province, Aggregates from Mount Merapi, Sleman Regency and Aggregates from Progo River, Kulon Progo Regency. The purpose of this study was to determine the use of aggregate types from these three locations in applications in high strength concrete. Aggregates are first tested for the physical and mechanical properties needed. The sample used in this study is cylindrical in size with a diameter of 15 cm with a height of 30 cm as many as 27 test objects. When the concrete is still fresh, a slump test is used to determine the workability value which is then tested for concrete compressive strength at the age of 7.14 and 28 days. From the results of this test, all concrete from these three locations can be used for high strength concrete above 50 MPa with aggregate from Progo River producing the highest concrete compressive strength.